Enlightened oversight of genetically engineered crops for the next generation. Issue 1 (19th February 2020) - Herman, Rod A.; Gaffney, Jim; Storer, Nicholas P.
Abstract: Risk‐disproportionate regulatory oversight has hampered the use of genetic engineering to sustainably improve crops for the duration of a human generation (≈25 years). There is scientific consensus that transgenic breeding methods are safe. Current regulations are often driven by unfounded public fear and hamper crop improvement that is critical to meeting current environmental and nutritional needs and future food security. The public good requires progressive nations to enact policies that enlighten the oversight of modern breeding methods so that current nutritional needs can be met, future food crises can be averted, and agriculture can become more sustainable.